2020
DOI: 10.1038/s41598-020-73071-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in skeletal muscles of Indian sheep with diverse carcass and muscle traits

Abstract: The study presents the miRNA profiles of two Indian sheep populations with divergent carcass and muscle traits. The RNA sequencing of longissimus thoracis muscles from the two populations revealed a total of 400 known miRNAs. Myomirs or miRNAs specific to skeletal muscles identified in our data included oar-miR-1, oar-miR-133b, oar-miR-206 and oar-miR-486. Comparison of the two populations led to identification of 100 differentially expressed miRNAs (p < 0.05). A total of 45 miRNAs exhibited a log2 fold cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…On the other hand, DP had an almost significant signal on BTA1: the gene closest to the SNP was SIM2 , already known to be associated with carcass quality, differentiation of longissimus, and semimembranosus muscle ( De Las Heras-Saldana et al, 2019 ; Edea et al, 2020 ). To conclude, the strongest of the remaining suggestively associated signals for DP came from BTA4, within LOC112446424 , a non-coding RNA close to candidate gene SLC13A4 , a cationic canal important both for muscle traits in sheep and growth and development in cattle ( Carvalho et al, 2020 ; Kaur et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, DP had an almost significant signal on BTA1: the gene closest to the SNP was SIM2 , already known to be associated with carcass quality, differentiation of longissimus, and semimembranosus muscle ( De Las Heras-Saldana et al, 2019 ; Edea et al, 2020 ). To conclude, the strongest of the remaining suggestively associated signals for DP came from BTA4, within LOC112446424 , a non-coding RNA close to candidate gene SLC13A4 , a cationic canal important both for muscle traits in sheep and growth and development in cattle ( Carvalho et al, 2020 ; Kaur et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…It is interesting to note that this activity is in turn dependent on MAPK and NFκβ signaling 27 . Recent studies on Bandur sheep have also reported the enrichment of the PI3K-Akt and MAPK pathways that are associated with hypertrophy as well muscle differentiation 12 , 13 . These pathways were enriched in the young animals.…”
Section: Discussionmentioning
confidence: 98%
“…Consumer preferences for Bandur sheep in India led to the investigation that established tenderness and higher backfat content in muscles of Bandur sheep as compared to local sheep found in the same area 12 . Our previous studies have attempted to understand the regulatory molecular mechanisms underlying the muscle traits in Bandur sheep breed in comparison to the local sheep 12 , 13 . These studies have identified the genes and pathways that may be associated with the muscling traits.…”
Section: Introductionmentioning
confidence: 99%
“…A miRNA, miR-192, was reported to regulate the myogenic differentiation and proliferation of skeletal muscle sheep satellite cells [ 44 ], which are responsible for producing myoblasts in skeletal muscle [ 118 ], through regulating the repression of retinoblastoma 1, which is a known regulator of myogenesis [ 119 ]. Additionally, miR-1, miR-133b, miR-206, and miR-486 were also reported to be differential expressed in the skeletal muscle of sheep and predicted to correlate with the development of skeletal muscle [ 120 ].…”
Section: The Mirnas Functions In Feed Efficiencymentioning
confidence: 99%